A Meta-Synthesis On Industrial Competency Needs And Vocational Higher Education Curriculum Transformation In The Metaverse Era - Andi Muhammad Irfan; Achmad Romadin; Fiskia Rera Baharuddin; Badaruddin Anwar; Mohd Zulfakar Bin Mohd Nawi (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – This study aims to examine the role of industrial competencies in strengthening vocational curricula in the metaverse era, particularly in response to the demands of Industry 4.0 and 5.0. The study argues that vocational education must move beyond conventional curriculum design by integrating technical, digital, and adaptive competencies aligned with specific industrial job positions.Methods – A qualitative multi-method design combined a multi-case study and qualitative meta-synthesis. Primary data were collected from industry partners and Universitas Negeri Makassar through interviews, observations, and document analysis. Secondary data came from relevant 2020–2025 studies on industrial competencies, vocational curriculum, immersive learning, and industry–education collaboration.Findings – The results show that production operators, technicians, CNC operators, and QC/QA officers require distinct competencies, including occupational safety, measurement, technical drawing, machining, CNC programming, product inspection, and quality improvement. Digital literacy, teamwork, critical thinking, adaptability, and problem-solving are also essential. Research implications – The study implies that vocational curriculum development should integrate immersive technology, personalized learning, and stronger link-and-match collaboration with industry through joint projects and hybrid classes. However, implementation may be limited by infrastructure, resources, and regulatory readiness.Originality – This study contributes a synthesized perspective on aligning industrial competencies, metaverse-based learning, and vocational curriculum transformation to prepare digitally adaptive and technically skilled graduates for high-tech industries.